Phenotypic and Genotypic Diversity of Ascochyta fabae Populations in Southern Australia - Blake, Sara N.; Lee, Robert C.; Russ, Michelle H.; Farquharson, Elizabeth A.; Rose, Jade A.; Herdina,; Goonetilleke, Shashi N.; Farfan-Caceres, Lina M.; Debler, Johannes W.; Syme, Robert A.; Davidson, Jennifer A. (Frontiers in Plant Science, 2022)
Industry reports of a shift in the foliar reaction of the ascochyta blight-resistant faba bean cultivar Farah in South Australia were made in 2014 and subsequent seasons. A second more virulent group of isolates was reported, and disease resistance ratings were downgraded for Farah. This study investigated phenotypic and genotypic diversity of the A. fabae population in southern Australia. The pathogenic variability of the A. fabae population was examined on a differential set of faba bean cultivars. This set was inoculated with 154 A. fabae isolates collected from 2015 to 2018 and a range of disease reactions from high to low aggressiveness was observed. Eighty percent of isolates collected from 2015 to 2018 were categorised as pathogenicity group (PG) 2 (pathogenic on Farah) and were detected in every region in each year of collection. Fourteen percent of isolates were non-pathogenic on Farah and designated as PG-1. A small group of isolates (16%) were pathogenic on the most resistant differential cultivars, PBA Samira or Nura, and these isolates were designated PG-3. Mating types of 311 isolates collected between 1991 and 2018 were determined and showed an equal ratio of MAT1 1 and MAT1 2 in the southern Australian population. The genetic diversity and population structure of 305 isolates was examined using DArTseq genotyping, and results suggest no association of genotype with any of the population descriptors viz: collection year, region, host cultivar, mating type or pathogenicity group. A Genome-Wide Association Study (GWAS) was performed to assess genetic association with pathogenicity traits and a significant trait-associated genomic locus for disease in Farah AR and PBA Zahra, and pathogenicity group (PG) was revealed. The high frequency of mating of A. fabae indicated by the wide distribution of the two mating types means changes to virulence genes would be quickly distributed to other genotypes. Continued monitoring of the A. fabae pathogen population through pathogenicity testing will be important to identify any increases in aggressiveness or emergence of novel pathogenicity groups. GWAS and future genetic studies using biparental mating populations could be useful for identifying virulence genes responsible for the observed changes in pathogenicity.